(untitled) (International Journal of Environmental Sciences, 2025)
Background: CKD in children is an emerging public health problem even in developing countries. In India, there is a lack of epidemiology in pediatric CKD; most of the cases present at a very advanced stage of the disease; the results are poor outcomes. Early detection and timely treatment are crucial in preventing disease progression. It tries to assess the incidence, clinical presentation, and etiological factors of pediatric CKD in children aged 1-14 years presenting at a tertiary care center in India, with an attempt to reflect upon the disease burden and necessity for early diagnosis and management. Methods: This is a prospective, observational study conducted between November 2016 and November 2018. Approximately 1,100–1,200 pediatric patients, aged between 1 and 14 years, with chronic kidney disease (CKD) were selected for data collection. CKD was defined as an estimated glomerular filtration rate (eGFR) of less than 60 ml/min/1.73 m² for a duration exceeding three months. The study was carried out at S.C.B. Medical College and Hospital, Cuttack, India. Data was collected on clinical presentation, laboratory findings, and etiological factors, followed by necessary analysis. Results: During the study, approximately 1,100–1,200 pediatric cases were evaluated, with 51 (about 4.2–4.6%) identified as having CKD. There was a male predominance among CKD cases, with males accounting for 62.74%. The age group most affected was 6–10 years, comprising 49.02% of CKD cases. Common clinical features in these pediatric patients included failure to thrive (100%), anemia (96.07%), and hypertension (64.70%). The primary causes of CKD were obstructive uropathy (43.13%) and renal dysplasia (31.37%). A large portion of patients presented with advanced CKD, as indicated by the fact that 45.09% were in Stage 5 at presentation. Dialysis was required in 41.17% of cases, with the majority (90.47%) receiving hemodialysis. Conclusion: The pediatric CKD in this cohort has features of late diagnosis and advanced disease at presentation. Obstructive uropathy and renal dysplasia were the leading causes. Early detection and early intervention are necessary to mitigate the progression of disease and improve outcomes. Improved access to renal care including pediatric renal transplantation is urgently needed in resource poor settings.